Evaluasi Usability Website Melalui Perancangan User Interface Menggunakan Metode Human Centered Design - Ardiansyah, Brian Nur; Mayasari, Rini; Jajuli, M. (Jurnal Ilmiah Wahana Pendidikan, 2025)
Kemala Bhayangkari 1 High School in Jakarta has utilized a website to manage data and information. However, the website still has various limitations in terms of performance and user interface design since it was first created. Based on user surveys and usability testing, many users expressed disappointment, confusion, and complaints regarding the website. This research aims to evaluate usability using the System Usability Scale (SUS) and to design a solution using Human-Centered Design (HCD). In this study, the method used to analyze the design is Human-Centered Design, with the goal of finding solutions to the website's problems. In the solution design testing phase, the System Usability Scale (SUS) method will be used, with a scoring range of 1-5. The test results show that the SUS score reached 76.87. According to the SUS benchmark, the comparison between the design before and after the redesign shows an improvement in user experience, from the marginal low category (below average) to Acceptable Good